Neighborhood social reciprocity and mental health among older adults in China: the mediating effects of physical activity, social interaction, and volunteering - Ruoyu Wang; Hongsheng Chen; Ye Liu; Yi Lu; Yao Yao (BMC, 2019)
Abstract Background This study aims to investigate the mechanisms through which neighborhood social reciprocity influences older adults' mental health in China. Methods This study used data from the 2011-2015 waves of the China Health and Retirement Longitudinal Study. It estimated the effects of neighborhood social reciprocity on older adults' mental health and tested the mediating effects of the frequencies of physical activity, social interaction with neighbors, and volunteering experience. Results The results indicated that more neighborhood social reciprocity related to better mental health. The effects of the three mediators were statistically significant and enhanced mental health. In addition, the effects of the mediators were strengthened by neighborhood social reciprocity, and vice versa. Conclusions In China, neighborhood social reciprocity influenced older adults' mental health directly and through the mechanisms of the frequencies of physical activity, social interaction with neighbors, and volunteering experience.